The Role of Mcl-1 in Embryonic Neural Precursor Cell Apoptosis - Flemmer, Robert T.; Connolly, Sarah P.; Geizer, Brittany A.; Opferman, Joseph T.; Vanderluit, Jacqueline L. (Frontiers in Cell and Developmental Biology, 2021)
Myeloid cell leukemia-1 (Mcl-1), an anti-apoptotic Bcl-2 protein, regulates neural precursor cell (NPC) survival in both the developing and adult mammalian nervous system. It is unclear when during the neurogenic period Mcl-1 becomes necessary for NPC survival and whether Bax is the sole pro-apoptotic target of Mcl-1. To address these questions, we used the nervous system-specific Nestin-Cre Mcl-1 conditional knockout mouse line (Mcl-1 CKO) to assess the anti-apoptotic role of Mcl-1 in developmental neurogenesis. Loss of Mcl-1 resulted in a wave of apoptosis beginning in the brainstem and cervical spinal cord at embryonic day 9.5 (E9.5) and in the forebrain at E10.5. Apoptosis was first observed ventrally in each region spreading with time dorsally. Within the spinal cord, apoptosis also spread in a rostral to caudal direction following the path of differentiation. Breeding the Mcl-1 CKO mouse with the Bax null mouse rescued the majority of apoptosis in the Mcl-1 CKO nervous system except in the dorsomedial brainstem and ventral thoracic spinal cord where Bax deletion only rescued 50% of apoptotic cells. This demonstrates that Mcl-1 promotes NPC survival primarily by inhibiting the activation of Bax, but that Bax is not the sole pro-apoptotic target of Mcl-1 during embryonic neurogenesis. Interestingly, although co-deletion of Bax rescued the majority of NPC apoptosis, it resulted in embryonic lethality at E13, whereas conditional deletion of both Mcl-1 and Bax rescued embryonic lethality. In summary, this study demonstrates the widespread dependency on Mcl-1 during nervous system development.